1999
DOI: 10.3109/09513599909167584
|View full text |Cite
|
Sign up to set email alerts
|

Estriol add-back therapy in the long-acting gonadotropin-releasing hormone agonist treatment of uterine leiomyomata

Abstract: The hypoestrogenic state induced by gonadotropin-releasing hormone agonists (GnRHa) has been shown to be effective in the treatment of uterine leiomyomas but to induce bone loss. Estriol has been described to be a weak and short-acting estrogen without an increased risk of endometrial proliferation and hyperplasia. The purpose of this study was to evaluate whether treatment of uterine leiomyomata with GnRHa plus oral estriol add-back therapy could prevent bone loss, without deteriorating the therapeutic effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
3

Year Published

2001
2001
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 23 publications
0
9
0
3
Order By: Relevance
“…The importance of in situ estrogen on leiomyoma growth may justify estrogen add-back therapy, in which small amounts of estrogen are administered during GnRH agonist therapy in an attempt to prevent adverse effects of long-term deprivation of estrogen, such as hot flashes and loss of bone mass, without nullifying their therapeutic effects (34,39,40). As discussed above, GnRH agonist (LA) therapy would render suppression of in situ aromatase a key determinant in achieving a maximum shrinkage of leiomyomas.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of in situ estrogen on leiomyoma growth may justify estrogen add-back therapy, in which small amounts of estrogen are administered during GnRH agonist therapy in an attempt to prevent adverse effects of long-term deprivation of estrogen, such as hot flashes and loss of bone mass, without nullifying their therapeutic effects (34,39,40). As discussed above, GnRH agonist (LA) therapy would render suppression of in situ aromatase a key determinant in achieving a maximum shrinkage of leiomyomas.…”
Section: Discussionmentioning
confidence: 99%
“…Dans une étude prospective randomisée, Nakayama et al ont rapporté l'évolution de 12 patientes porteuses de myome et initialement traitées par agonistes de la GnRH seuls (n = 6) ou auxquels étaient associés 4 mg d'estriol par jour pendant quatre mois, deux mois après l'injection d'agonistes (n = 6) [45]. Après deux mois, la réduction du volume des fibromes était similaire dans les deux groupes (environ 50 à 60 %), mais elle se poursuivait dans le groupe agonistes de la GnRH seuls (avec une réduction totale de 30 %) et restait identique dans le groupe dans lequel de l'estriol était ajouté à deux mois.…”
Section: Association Estroprogestativeunclassified
“…A recent study [49] carried out on a small number of subjects demonstrated that estradiol administration after 2 months of GnRH analog treatment alone is effective in reducing bone loss and vasomotor symptoms without compromising the efficacy of treatment with an analog alone.…”
Section: Add-back Therapymentioning
confidence: 99%